Low-molecular-weight heparin modulates vein wall fibrotic response in a plasminogen activator inhibitor 1-dependent manner - Obi, Andrea T. (J Vasc Surg Venous Lymphat Disord, 2014)
BACKGROUND: Treatment with low-molecular-weight heparin (LMWH) favorably alters the vein wall response to deep venous thrombosis (DVT), although the mechanisms remain unclear. Previous studies have suggested that LMWH alters the levels of circulating plasminogen activator inhibitor 1 (PAI-1), a known mediator of fibrosis, and may improve endogenous fibrinolysis. We hypothesized that LMWH favorably alters the vein wall response by binding of PAI-1 and acceleration of fibrinolysis. METHODS: Wild-type and PAI-1 (−/−) mice underwent treatment with LMWH after induction of occlusive DVT. Vein wall and plasma were harvested and analyzed by enzyme-linked immunosorbent assay, zymography, real-time polymerase chain reaction, and immunohistochemistry. RESULTS: Wild-type mice treated with LMWH exhibited diminished vein wall fibrosis (0.6 ± 0.6 vs 1.4 ± 0.2; P < .01; n = 5) and elevation of circulating PAI-1 (1776 ± 342 vs 567 ± 104 ρg/mL; P < .01; n = 5) compared with untreated controls after occlusive DVT. PAI-1(−/−) mice treated with LMWH were not similarly protected from fibrosis, despite improved thrombus resolution. Treatment with LMWH was associated with decreased intrathrombus interleukin-lβ (68.6 ± 31.0 vs 223.4 ± 28.9 ρg/mg total protein; P < .01; n = 5) but did not alter inflammatory cell recruitment to the vein wall. PAI-1 (−/−) mice exhibited significantly elevated intrathrombus (257.2 ± 51.5 vs 4.3 ± 3.8 ρg/mg total protein; n = 5) and vein wall interleukin-13 (187.2 ± 57.6 vs 9.9 ± 1.1 ρg/mg total protein; P < .05; n = 5) as well as vein wall F4/80 positively staining monocytes (53 ± 11 vs 16 ± 2 cells/5 high-power fields; P < .05; n = 4). CONCLUSIONS: LMWH did not accelerate venous thrombosis resolution but did protect against vein wall fibrosis in a PAI-1-dependent manner in an occlusive DVT model. Lack of PAI-1 correlated with accelerated venous thrombosis resolution but no protection from fibrosis. PAI-1 inhibition as a treatment strategy for DVT is likely to accelerate clearance of the thrombus but may come at the expense of increased vein wall fibrosis. CLINICAL RELEVANCE: The pathophysiologic mechanism of post-thrombotic syndrome is not well understood clinically or experimentally. In this study, we evaluated the effect of the prominent fibrinolytic mechanism, plasminogen activator inhibitor 1 (PAI-1), and low-molecular-weight heparin (LMWH) on vein wall injury after thrombosis. We show here that LMWH is protective from vein wall fibrosis, but this is abrogated in PAI-1-deleted mice. This is also correlated with monocyte vein wall influx. These data support the clinical observation that LMWH may be protective from post-thrombotic vein wall injury in a PAI-1-dependent manner.